2021
DOI: 10.1016/j.scr.2021.102218
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular effects of TNF-α on human iPSC-derived cardiomyocytes

Abstract: Proinflammatory molecule tumor necrosis factor alpha (TNF-α) is predominantly elevated in cytokine storm as well as worsening cardiac function. Here we model the molecular and functional effects of TNF-α in cardiomyocytes (CMs) derived from human induced pluripotent stem cells (hiPSC). We found that treatment of hiPSC-CMs with TNF-α increased reactive oxygen species (ROS) and caspase 3/7 activity and caused cell death and apoptosis. TNF-α treatment also resulted in dysregulation of cardiomyocyte function with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…ISS mG samples had more cells with normal Ca 2+ transients compared with ISS 1G samples (93% in ISS mG cells versus 78% in ISS 1G cells) (Figure 5B). The proportion of the cells with abnormal Ca 2+ transients and the types of abnormal Ca 2+ transients in ISS 1G cultures were comparable with typical hiPSC-CM cultures in ground-based studies (Forghani et al, 2021;Lan et al, 2013;Liu et al, 2020a;Saraf et al, 2021). Most of these abnormal cells had minor abnormality with inconsistent beating period (type B) and a few cells had transients with a single notch of additional Ca 2+ spike (diastolic Ca 2+ signal) before the following Ca 2+ transient had initiated (type A) (Figures 5A and 5B).…”
Section: Resultssupporting
confidence: 54%
“…ISS mG samples had more cells with normal Ca 2+ transients compared with ISS 1G samples (93% in ISS mG cells versus 78% in ISS 1G cells) (Figure 5B). The proportion of the cells with abnormal Ca 2+ transients and the types of abnormal Ca 2+ transients in ISS 1G cultures were comparable with typical hiPSC-CM cultures in ground-based studies (Forghani et al, 2021;Lan et al, 2013;Liu et al, 2020a;Saraf et al, 2021). Most of these abnormal cells had minor abnormality with inconsistent beating period (type B) and a few cells had transients with a single notch of additional Ca 2+ spike (diastolic Ca 2+ signal) before the following Ca 2+ transient had initiated (type A) (Figures 5A and 5B).…”
Section: Resultssupporting
confidence: 54%
“…The components of inflammatory mediators include TNF-α and the IL-1 family and the IL-6 family, which are the focus of the current research [3]. Previous studies have confirmed that these proinflammatory cytokines can be expressed by all nucleated cell types residing in the myocardium, including cardiomyocyte [31]. The overexpression of cytokine cascades contributes to HF progression [3].…”
Section: Discussionmentioning
confidence: 95%
“…Specifically influencing the mechanical activity of cardiac cells, such effects include direct posttranslational modifications of proteins of the excitation-contraction coupling machinery. Prolonged imbalance in the redox state of cardiomyocytes leads to instable Ca 2+ handling and arrhythmogenic modifications [ 42 , 43 ]. Moreover, disorders of Ca 2+ handling and Ca 2+ overload influence Cx43 channel function.…”
Section: Discussionmentioning
confidence: 99%